Fertiseeder, a manual seeder cum fertilizer micro-dose applicator in Madagascar - CGIAR Research Program on Rice (2021)
Fertiseeder was tested on-station and on-farm in Madagascar. In 2018, the fertiseeder was demonstrated to 222 farmers and their opinions were collected for improvement. The fertiseeder was further improved based on the farmers' feedback. The new improved model was again tested in the 2019-2020 and ready for out-scaling in Madagascar.